Cytokine inflammation state in non-alcoholic steatohepatitis surpasses that of chronic hepatits C and alcoholic liver disease - Cordero Pérez, Paula; Martínez Macías, R. M.; Cura Esquivel, Idalia Aracely; Gutiérrez Reyes, Gabriela; Gutiérrez Ruiz, M.C.; Torres González, Liliana; Muñoz Espinosa, Linda Elsa (Academia Publisshing, 2017)
Increased serum levels of cytokines were reported in persistent inflammatory conditions such as non-alcoholic steatohepatitis (NASH), chronic hepatitis C (CHC) and alcoholic liver disease (ALD). The aim of this study was to compare cytokines IL-6, TNF-α, VEGF, EG-VEGF, BB-PDGF and ICAM-1 levels in these patients. Ninety patients seen in two Mexican outpatient clinics (Liver Unit, UANL and HIPAM and UNAM) were included: NASH (30), CHC (30) and ALD (30). Serum cytokines IL-6, TNF-α, VEGF, EG-VEGF, BB-PDGF and ICAM-1 were measured by ELISA. A statistically significant difference was found in 5/6 mediators studied in NASH patients vs. CHC and ALD. Regarding ICAM-1 (5.482±613 vs. 2.145±1011 vs. 1.830±1224 pg/mL; P<0.05; respectively), IL-6 (2.430±1506 vs. 726±735 vs. 516±603 pg/mL; P<0.05, respectively), TNF-α (3686±1409 vs. 677±747 vs. 437±70 pg/mL; P<0.05; respectively), VEFG (2.267±486 vs. 421±557 vs. 554±619 pg/mL; P<0.05; respectively) and EG-VEGF (2.146±1914 vs. 1.225±1388 vs. 799±1046 pg/mL; P<0.05; respectively). VEGF positively correlated with TNF-α(r+0.51 and P=0.004) in NASH and negatively in CHC (r-0.44 and P=0.01). The only positive correlation for BB-PDGF was with EG-VEGF levels (r=+0.41 and P=0.02). IL-6 exhibited a positive correlation vs. ICAM-1 in ALD (r+0.42 and P=0.02). We demonstrated a significant increase in pro-inflammatory cytokines (TNF-α, IL-6, VEGF and EG-VEGF) and ICAM-1 in patients with NASH. Correlations showed differential cytokine and adhesion molecule patterns on the basis of the liver disease etiology. These abnormalities in cytokine profile can influence the pathophysiology of liver injury.